2009
DOI: 10.1038/sc.2009.52
|View full text |Cite
|
Sign up to set email alerts
|

A review of published reports on neuroprotection in spinal cord injury

Abstract: Study design: Literature review. Objectives: To review the main published current neuroprotection research trends and results in spinal cord injury (SCI). Setting: This paper is the result of a collaboration between a group of European scientists. Methods: Recent studies, especially in genetic, immune, histochemical and bio (nano)-technological fields, have provided new insight into the cellular and molecular mechanisms occurring within the central nervous system (NS), including SCIs. As a consequence, a new s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 55 publications
(53 reference statements)
0
40
0
Order By: Relevance
“…However, the clinical translation of ChABC may be set back by two major challenges: (1) its poor thermostability and (2) its synthesis from an Escherichia coli origin, which may carry immunological risk [114,115] . in addition to ChABC, there is evidence that MMPs can degrade the protein backbone of some CSPGs to restrict the formation of a glial scar [116] , and the process is associated with mitigation of a functional deficit; however, axonal dieback is an unpleasant secondary response [117] .…”
Section: Pharmacological Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the clinical translation of ChABC may be set back by two major challenges: (1) its poor thermostability and (2) its synthesis from an Escherichia coli origin, which may carry immunological risk [114,115] . in addition to ChABC, there is evidence that MMPs can degrade the protein backbone of some CSPGs to restrict the formation of a glial scar [116] , and the process is associated with mitigation of a functional deficit; however, axonal dieback is an unpleasant secondary response [117] .…”
Section: Pharmacological Strategiesmentioning
confidence: 99%
“…it is well-established that chondroitinase ABC (ChABC) significantly ameliorates the hostile-matrix microenvironment following SCI by enzymatically digesting the glycosaminoglycan side-chains of CSPGs and promotes functional recovery [4,111,112] . in accord with these findings, a recent study showed that the infusion of ChABC is also successful in restoring neuronal glycosylation to normal [113] .However, the clinical translation of ChABC may be set back by two major challenges: (1) its poor thermostability and (2) its synthesis from an Escherichia coli origin, which may carry immunological risk [114,115] . in addition to ChABC, there is evidence that MMPs can degrade the protein backbone of some CSPGs to restrict the formation of a glial scar [116] , and the process is associated with mitigation of a functional deficit; however, axonal dieback is an unpleasant secondary response [117] .…”
mentioning
confidence: 97%
“…Regarding the primary lesions pathways and topographic-related issues, 'the critical velocity of tissue movement, which will lead to an axonal tear in a spinal cord contusion, is 0.5-1 m s − 1 , concentrating most of the stretching and shearing forces in the central part'. 29,30 MRI control 31 was mandatory in patient no. 5, with a symptomfree interval followed by neurological deterioration, and in patients no.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Despite the tremendous efforts made, scientists have failed to fully understand the secondary destructive process and all protection measures have not succeeded in preventing it from progressing. 21 The use of mega dose of methylprednisolone recommended by the NASCAS II and III studies have Figure 3 The hippocampus and amygdala of the limbic system (courtesy of http://pubs.niaaa.nih.gov/publications/arh284/images/ tapert.gif).…”
Section: Lesion-induced Responsementioning
confidence: 99%